Agroecological fruit plant nurseries and zoonosis prevention as food safety alternative - Alayón Luaces, Paula (2020)
Fil: Alayón Luaces, Paula. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.